Strategi Pembelajaran Blended Learning terhadap Kemampuan Konsep dan Prosedur Physical Examination pada Mahasiswa Keperawatan - Nurul Laili; Wahyu Tanoto (Indonesian Journal of Learning Education and Counseling, 2020)
The research objective was to determine the comparison of students' abilities in understanding concepts and procedures using the blended learning method. The research method used is a quasi experimental design with a post-test-only non-equivalent control group approach, the analysis technique uses the Mann-Whitney test by comparing the results of student scores between those using conventional learning methods and those using blended learning, the research results are that there are differences. meaningful (p-value = 0,000). Blended learning is effective for improving student learning outcomes in understanding concepts (cognitive) and procedures (skills / psychomotor). The balance between the use of educational technology with conventional learning / humanistic interactions has a positive impact on motivation and the achievement of the expected abilities and competencies in learning.